PENERTIBAN LALU LINTAS DAN ANGKUTAN JALAN DI KOTA PEKANBARU - Saputra, Angga; Rusli, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Action is an important step to do, given the problems of Metropolitan city located on undisciplined in the traffic and the traffic jams and road transport. The city of Pekanbaru, leading metropolitan cities certainly have to take a stand, so that the problems occurred in the citys metropolitan doesnt happen anyway in the city of Pekanbaru. The action performed by Satlantas Polresta together Dishubkominfo Pekanbaru has not felt up to due to the still large number of cases of violations and traffic accidents and congestion that occurred. The purpose of this research is to know how the implementation of curbing traffic and road transport performed by Satlantas Polresta together Dishubkominfo Pekanbaru and to determine the factors that influence the implementation of curbing traffic and road transport in the city of Pekanbaru.The concept of the theory of management and use is the author of management oversight. This research uses qualitative research methods to the study of descriptive data. In data collection, the author uses interview techniques, observation and documentation. With the use of key informants as a source of information and technique of triangulation as a source in the validity of the data.The results of this research indicate that curbing traffic and road transport in the city of Pekanbaru were done by Satlantas Polresta and Dishubkominfo the city of Pekanbaru, yet feels maximum, evidenced from the still high number of violations and accidents that occur each year, weak internal surveillance officers in the field, so there are still officers who commit irregularities for personal gain. The factors that inhibit the action of traffic and road transport in the city of Pekanbaru is the number of officers who conduct surveillance system, still less the budget hasnt been right on target as well as lack of knowledge and awareness of good and safe driving.Keywords: Curbing, traffic and Road Transport